Bulk-Palladium and Palladium-on-Gold Electrocatalysts for the Oxidation of Hydrogen in Alkaline Electrolyte. Issue 1 (1st January 2015) - Henning, Sebastian; Herranz, Juan; Gasteiger, Hubert A.
Abstract : The commercial feasibility of alkaline-exchange membrane fuel cells and electrolyzers passes by the development of hydrogen oxidation and evolution reaction (HOR/HER) catalysts featuring an activity and/or cost advantage over platinum, which remains the most active metal for these processes. Among these alternatives, Pd appears as a promising candidate, since its price is typically 2–3 fold lower than that of Pt. With this motivation, the first section of this study displays our attempts at quantifying the kinetic parameters of the HOR/HER on bulk Pd in 0.1 M NaOH, which were prevented by the simultaneous absorption of hydrogen into bulk palladium. We succeeded at circumventing this issue by depositing Pd-adlayers on a polycrystalline Au-substrate by galvanic displacement of underpotentially-deposited Cu or by electrochemical plating of Pd 2+ . The resulting surfaces appear to consist of three-dimensional Pd-structures of an unknown thickness that we believe to scale with the palladium coverage, θPd/Au . This last parameter is inversely proportional to the HOR/HER-activity of the Pd-on-Au surfaces, in agreement with numerous theoretical and experimental studies in acid media that correlate this effect to the tensile strain induced by the Au-substrate on the Pd-lattice.